Hydroquinone Levels in Whitening Body Lotion Circulating in Makassar City by the UV-Vis Spectrophotometry Method - Rezky M, Mega; Suhaenah, Asriani; Baits, Muzakkir (Pharmaceutical Reports, 2023)
Hydroquinone is an active compound that is able to control pigment production to inhibit melanin formation and has activity as a skin whitening agent, so hydroquinone is widely used in cosmetic products. Hydroquinone has adverse side effects if used for a long time. BPOM RI has issued a regulation on the prohibition on the use of hydroquinone as a bleach in cosmetics. The purpose of this study was to identify the hydroquinone content in whitening handbody samples circulating in Makassar City and to find out the level of hydroquinone contained in the sample. Qualitative analysis is carried out using FeCl₃ reagents and quantitative analysis using the UV-VIS spectrophotometry method. The number of samples used in this study was as many as 4 samples that did not have a registration number from BPOM RI. The results showed that the 4 samples studied positively contained hydroquinone. The results of the sample test measured at a maximum wavelength of 292 nm, obtained hydroquinone levels at the sample code HB1 = 1.267%; sample code HB2 = 0.912%; sample code HB3 = 0.379% and sample code HB4 = 0.449%.